2015
DOI: 10.1016/j.nanoen.2015.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Tuning thermal conductance across sintered silicon interface by local nanostructures

Abstract: A large reduction of heat conduction through silicon-silicon sintered interface by local oxide nanostructures is quantitatively demonstrated by a newly developed method to directly measure thermal boundary conductance across bonded interfaces. Together with the theoretical analysis that relates the thermal boundary conductance to thermal conductivity of densely-packed bulk nanocrystalline silicon, we identify a route to significantly reduce the thermal conductivity from the state-of-art value, even to approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Since electron contribution to thermoelectric properties is determined by Θ(E) as shown in Eqs. (2)- (7), the change in Θ(E) due to defects are discussed here. Figure 3 shows Θ(E) of 100-nm CNTs for (a) vacancies and (b) SW defects with σ varying from 0.0% (blue line) to 0.1% (red line) with the equal interval of σ (corresponding to Ndef = 0 to 9).…”
Section: A Transmission Functionmentioning
confidence: 99%
“…Since electron contribution to thermoelectric properties is determined by Θ(E) as shown in Eqs. (2)- (7), the change in Θ(E) due to defects are discussed here. Figure 3 shows Θ(E) of 100-nm CNTs for (a) vacancies and (b) SW defects with σ varying from 0.0% (blue line) to 0.1% (red line) with the equal interval of σ (corresponding to Ndef = 0 to 9).…”
Section: A Transmission Functionmentioning
confidence: 99%
“…In this sense, Casimir limit is no longer an appropriate reference since it does not account for frequency dependent phonon transmission/reflection at the interface that can be strongly altered by the interfacial structures. Thermal transport across a sintered Si-Si interface has been investigated by Sakata et al 14 , and SiOx nano-precipitates formed at the interface were found to give rise to an order-of-magnitude controllability. Hence, there is a room to further reduce thermal conductivity by nanometer sized grains and precisely controlled interfaces, however, sintering, being a high energy process, has limitation due to the grain growth and interfacial diffusion/mixing.…”
mentioning
confidence: 99%
“…29 The value of c is determined so as to match model and experiment for the thermal boundary conductance, G, which is a measurable quantity for instance by the time domain thermoreflectance method. 42 From the Landauer formula, G can be expressed as 25,43 …”
mentioning
confidence: 99%
“…Using the measured thermal boundary conductance of sintered silicon interfaces ranging from around 100 to 1000 MWm À2 K À1 depending on the sintering conditions, 42 we obtain the lower and upper bounds of c, 2.40 and 26.8.…”
mentioning
confidence: 99%